The Henstock-Stieltjes Integral for $n$-dimensional Fuzzy-Number-Valued Functions - Muawya Elsheikh Hamid; Luoshan Xu; Zengtai Gong (International Journal of Mathematics And its Applications, 2017)
In this paper, the concept of ($FHS$) integral for $n$-dimensional fuzzy-number-valued functions is presented, several necessary and sufficient conditions of integrability for $n$-dimensional fuzzy-number-valued functions are given by means of this concept.